Comparison of Ultrasound-Guided Fine-Needle Cytology Quality in Thyroid Nodules with 22-, 23-, and 25-Gauge Needles - YiJie Dong; LiLi Gao; Yang Sui; MinJing Mao; WeiWei Zhan; JianQiao Zhou (Analytical Cellular Pathology)
Objective. To compare the cytology quality of ultrasound-guided fine-needle biopsy in thyroid nodules with 22-, 23-, and 25-gauge (G) needles prospectively. Methods. A total of 240 consecutive nodules underwent ultrasound-guided fine-needle aspiration (USG-FNA) and 240 nodules underwent ultrasound-guided fine-needle capillary (USG-FNC) were included in this prospective study from October 2014 to February 2016. Each nodule was sampled using 22 G, 23 G, and 25 G needle according to designed orders, and 1240 smears were finally obtained. Cytology quality was scored by a cytologist blinded to needle selection. Results. In USG-FNA, the average scores and standard deviations were 5.50±2.87 for 25 G needles, 4.82±2.95 for 23 G needles, and 5.19±2.81 for 22 G needles. In USG-FNC, the average scores and standard deviations of each group were 5.12±2.69 for 25 G, 4.60±2.90 for 23 G, and 4.90±2.90 for 22 G needles. The specimen quality scores of 25 G group were significantly higher than that of 23 G group (P<0.017) in both USG-FNA and USG-FNC. However, the differences were not statistically significant in nondiagnostic rate using different gauge of needles (P>0.017 for all). Conclusions. 25 G needles obtained the highest scores of sample quality in thyroid FNA and FNC comparing with 22 G and 23 G needles. 25 G needle should be first choice of thyroid FNA and FNC in routine work.